Caracterização morfológica e citológica de gérbera : subsídio para o melhoramento genético - Cardoso, Raquel Dalla Lana (2007)
The Brazilian production of gerbera (Gerbera hybrida Hort.) is entirely dependent of seedlings import of multinational companies, what could be reduced with the new hybrid competitive production. For that, it is necessary the development of basic knowledge about the species, such as: reproduction form, floral morphology, pollination and, mainly, evaluation of the natural genetic variability existent. This work was conducted with the objective of to furnish subsidies for the gerbera improvement in Brazil, providing to the producers new alternatives forms to the extreme dependence to the multinationals. Thirteen gerbera accesses, being six cultivars (G. hybrida) and seven non commercial accesses (Gerbera sp.) were cultivated in semi-protected atmosphere and appraised in four different studies: characterization and genetic divergence based on morphologic markers, determination of the sexual expression and reproductive system, cytogenetics characterization, pollen viability and artificial hybridization, and efficiency of different methods of extraction of DNA genômico seeking the use in molecular markers. The morphological data were submitted to the multivariated analysis and variance. With the multivariated analysis was possible to verify the existence of genetic variability in gerbera that s could be useful to improvement programs. In gerbera there are three types of flowers: flowers of the ray and trans (feminine) and the disk flower (hermaphrodite). The hybridization among the cultivars and non commercial accesses is possible due to they possess compatible genome, what was verified in the cytogenetics characterization (2n = 50) and confirmed trough seeds production in crossings among they, and due the average percentage of pollen viability be high, 89,6%. It was verified that is not necessary to emasculate hermaphrodite flowers for crossing and that there is not apomitic indications in the evaluated accesses. The obtention good quality pattern and amount of genomic DNA with the method CTAB 2% indicates that it is an efficient methodology, to use in molecular markers as a way to access the genetic variability at molecular level